Communism and popular culture in the 20th Century. - Montagu, Ivor Goldsmid Samuel, 1904-1984; Archive Trust of the Communist Party of Great Britain (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2021)
Ivor Montagu (1904-1984) was best known for his work as a filmmaker, scriptwriter, and producer. He was also a trained naturalist, the founder of the International Table Tennis Federation, president of the Southampton F.C. Supporters’ Club, and an active member of the Communist Party of Great Britain (CPGB). This collection contains Montagu’s personal, political, and professional papers. Of particular interest is his correspondence with prominent public figures such as Alfred Hitchcock, Bernard Shaw, and Solly Zuckerman. Montagu’s papers are a useful resource for students and scholars who are interested in the impact of communism on British popular culture and vice-versa.
Date range: 1900-1999.
Keywords: Montagu, Ivor Goldsmid Samuel, -- 1904-1984.; Montagu, Ivor Goldsmid Samuel, -- 1904-1984 -- Correspondence; Communism and culture -- Great Britain -- History -- 20th century; Communism and society -- History -- 20th century